Spatial and Temporal Variations in Fire Frequency in the Boreal Forest of Northern Alberta - Larsen, Christopher Poul Storm (1994)
Forest fires occur frequently in the boreal forest of North America and greatly affect vegetation dynamics, biogeochemical cycles and resident human populations. Estimates of the frequency of boreal forest fires would be useful for understanding boreal ecosystems and managing the affects of fires on human populations. The objectives of this work were to investigate relations between fire frequency and climate change, vegetation)n type and waterbreaks in Wood Buffalo National Park (WBNP), located in northern Alberta. To address these objectives, four hypotheses were tested: 1) tree ring-width records from the boreal forest can provide a proxy climate record; 2) annual area burned in the boreal forest varies in response to climate changes; 3) boreal fores: fire frequency varies with differences in forest type and the proximity to waterbreaks and 4) fossil pollen and macroscopic charcoal records from massive lake sediments can provide meaningful estimates of local fire frequency. The first hypothesis was tested by constructing tree ring chronologies from 3 white spruce and two jack pine sites in WBNP. All five chronologies were significantly positively correlated with June precipitation in the growth year or the previous year, and were significantly negatively correlated with historical records of fire weather and annual area burned. The second hypothesis was tested by analyzing historical records of annual area burned and climate. and tree ring records of fire history and climate. Annual area burned was significantly negatively correlated with seasonal means of fire weather indices. The time since last fire was estimated using tree ring records from 166 sites located throughout WBNP. These records exhibited decadal and centennial scale variations in fire frequency. Comparisons with tree ring other proxy climate records suggest that the~e variations are related to climatic changes. The third hypothesis was tested using survival analysis of the time since last fire records, disaggregated by dominant vegetation and ...